I would like to know how to evaluate $$\sum\limits_{r=1}^\infty(-1)^{r+1}\frac{\cos(2r-1)x}{2r-1}$$

There are a couple of issues I have with this. Firstly, depending on the value of $x$, it seems, at least numerically, that this value is always $$\pm\sqrt{\frac{\sqrt5-1}{2}}$$ If this is true, how would I prove this?

Secondly, I tried using complex numbers to evalaute this, as shown briefly below:

$$C=\sum\limits_{r=1}^\infty(-1)^{r+1}\frac{\cos(2r-1)x}{2r-1}$$ $$S=\sum\limits_{r=1}^\infty(-1)^{r+1}\frac{\sin(2r-1)x}{2r-1}$$ $$\implies C+iS=\arctan e^{ix}$$ on using the power series of $\arctan x$. Differentiating yields a completely imaginary number: $$\frac{i}{2}\sec x$$ which proves that the value of $C$ is a constant. However, this gives me no information whatsoever on the value of $C$.

Thank you for your help.

  • $\begingroup$ Why would you want the exact value of this series? Or are you only interested in some "properties" of this series? $\endgroup$
    – user9464
    Jan 16, 2021 at 23:40
  • $\begingroup$ @mrsamy I'm just looking at it out of curiosity. $\endgroup$ Jan 16, 2021 at 23:41
  • 1
    $\begingroup$ That's a fair reason :-) $\endgroup$
    – user9464
    Jan 16, 2021 at 23:41
  • $\begingroup$ Have you studied some Fourier Series, perhaps in advanced analysis...or harmonic analysis...or stuff? $\endgroup$
    – DonAntonio
    Jan 17, 2021 at 0:41
  • $\begingroup$ @DonAntonio unfortunately not; I am still in high school and don't know a lot beyond the high school curriculum. $\endgroup$ Jan 17, 2021 at 9:35

3 Answers 3


As you noted, the real part of the sum, $C$, is constant no matter what the value of $x$ (so long as $x$ is real). Thus plug in $x = 0$

$$C = \operatorname{Re}(\arctan e^{i0}) = \frac{\pi}{4}$$

  • 1
    $\begingroup$ Thanks so much! However, it seems that $C$ can take different values; namely $$\pm\frac{\pi}{4}$$ at least according to desmos. How do I obtain the negative value? $\endgroup$ Jan 16, 2021 at 23:48
  • $\begingroup$ ... no matter what the value of $x$... - not quite (replace $x$ by $x+\pi$ in the original series to see what actually happens). And... actually we reinvent this... or more specifically this. $\endgroup$
    – metamorphy
    Jan 16, 2021 at 23:50
  • $\begingroup$ @metamorphy I see, thanks for the clarification! $\endgroup$ Jan 16, 2021 at 23:52
  • $\begingroup$ @A-LevelStudent the sum changes values at $x=\frac{\pi}{2}$ because arctan is undefined at $i$. It's like what happens with the graph of $\arctan(2\tan x)$ at the same points. But thanks for pointing it out, I would not have caught that otherwise. $\endgroup$ Jan 16, 2021 at 23:55
  • $\begingroup$ Why isn't $\arctan$ defined at $i$? Isn't it just equal to $i~\text{artanh}1$? $\endgroup$ Jan 16, 2021 at 23:56

The Series

This series only converges for $x\in\mathbb{R}$. If $x\not\in\mathbb{R}$, the terms do not go to $0$.$\newcommand{\sgn}{\operatorname{sgn}}\newcommand{\Re}{\operatorname{Re}}\newcommand{\Im}{\operatorname{Im}}$ $$ \begin{align} &\sum_{r=1}^\infty(-1)^{r+1}\frac{\cos((2r-1)x)}{2r-1}\tag{1a}\\ &=\frac12\sum_{r=1}^\infty(-1)^{r+1}\frac{e^{i(2r-1)x}}{2r-1}+\frac12\sum_{r=1}^\infty(-1)^{r+1}\frac{e^{-i(2r-1)x}}{2r-1}\tag{1b}\\ &=\frac12\tan^{-1}\left(e^{ix}\right)+\frac12\tan^{-1}\left(e^{-ix}\right)\tag{1c}\\[9pt] &=\Re\left(\tan^{-1}\left(e^{ix}\right)\right)\tag{1d}\\[12pt] &=\frac\pi4\,\sgn(\cos(x))\tag{1e} \end{align} $$ Explanation:
$\text{(1b)}$: $\cos(x)=\frac12\left(e^{ix}+e^{-ix}\right)$
$\text{(1c)}$: power series for $\tan^{-1}(z)$
$\text{(1d)}$: $\tan(\bar z)=\overline{\tan(z)}$
$\text{(1e)}$: $|\tan(z)\,|=1$ when $\Re(z)=\pm\frac\pi4$
$\phantom{\text{(1e):}}$ and $\Re(\tan(z))$ has the same sign as $\Re(z)$
$\phantom{\text{(1e):}}$ also, if $\cos(x)=0$, all the terms of the series are $0$

Concerning $\boldsymbol{\tan(x+iy)}$

Note that $$ \begin{align} \tan(x+iy)&=\frac{\sin(x)\cosh(y)+i\cos(x)\sinh(y)}{\cos(x)\cosh(y)-i\sin(x)\sinh(y)}\tag{2a}\\ &=\frac{\sin(x)\cos(x)+i\sinh(y)\cosh(y)}{\cos^2(x)\cosh^2(y)+\sin^2(x)\sinh^2(y)}\tag{2b} \end{align} $$ is on the unit circle when the absolute values of the numerator and denominator are equal. Since $\cosh^2(y)-\sinh^2(y)=1$, equation $\text{(2a)}$ says that is when $$ \begin{align} \sin^2(x)\cosh^2(y)+\cos^2(x)\sinh^2(y)&=\cos^2(x)\cosh^2(y)+\sin^2(x)\sinh^2(y)\tag{3a}\\[6pt] \sin^2(x)&=\cos^2(x)\tag{3b} \end{align} $$ Thus, $|\tan(z)\,|=1$ when $\Re(z)=\pm\frac\pi4$

Furthermore, equation $\text{(2b)}$ says not only that $\tan(\bar z)=\overline{\tan(z)}$, but also that, when $\Re(z)=\pm\frac\pi4$, $\Re(\tan(z))$ has the same sign as $\Re(z)$.

enter image description here


I've learned some new related facts since posting the question, one of which solves this very simply. The relevant formula, stated below, can be found by using the fact $\arctan z=-i\operatorname{artanh} iz$. $$\arctan(x+iy)=\frac{1}{2}\arctan\frac{2x}{1-x^2-y^2}+\frac{i}{2}\operatorname{artanh}\frac{2y}{1+x^2+y^2}$$ Plugging in $x=\cos x$ and $y=\sin x$ we find that $$\arctan e^{ix}=\frac{1}{2}\arctan(\pm\infty)+\frac{i}{2}\operatorname{artanh}\sin x$$ And thus $$C=\pm\frac{\pi}{4}$$


You must log in to answer this question.

Not the answer you're looking for? Browse other questions tagged .